2004
DOI: 10.1177/1531244504421004
|View full text |Cite
|
Sign up to set email alerts
|

Critical Aspects of Parenting Plans for Young Children: Interjecting Data into the Debate about Overnights

Abstract: The debate about the benefits and drawbacks of overnight schedules for young children is hotly contested in family law. This study investigated connections between occurrence of overnights, schedule consistency, number ofcaregivers, and young children's adjustment to parental separation and divorce. Families ( N = 161) with children aged 6 years or younger were recruited at the time of filing for divorce or child custody (if unmarried); follow-up data were obtained from 132 families IS to 18 months later. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 10 publications
2
56
0
2
Order By: Relevance
“…More frequent overnights were associated with more behavior problems in some analyses, but the results were not statistically significant. Finally, with one exception (father-reported social problems), the better child adjustment associated with more frequent overnights was no longer statistically significant after accounting for sociodemographic and family relationship factors (Pruett, Ebling, & Insabella, 2004). …”
Section: A Limited Research Basementioning
confidence: 92%
“…More frequent overnights were associated with more behavior problems in some analyses, but the results were not statistically significant. Finally, with one exception (father-reported social problems), the better child adjustment associated with more frequent overnights was no longer statistically significant after accounting for sociodemographic and family relationship factors (Pruett, Ebling, & Insabella, 2004). …”
Section: A Limited Research Basementioning
confidence: 92%
“…Despite this, concern continues to be expressed that overnight contact with the non-resident parent may be harmful to an infant's attachment security because it denies ongoing, constant access to the primary attachment figure (R. Bowlby & McIntosh, 2011;George, Solomon, & McIntosh, 2011). By contrast, others argue that overnight contact with the non-resident parent is not necessarily harmful and may even be beneficial to attachment security because it preserves the infant's close relationships with two, equally important and often complementary, attachment figures (Amato & Gilbreth, 1999;Ludolph, 2012;Pruett, Ebling, & Insabella, 2004;Warshak, 2014). Overnight contact with the non-resident parent is important because, with fewer time constraints, it promotes authoritative parenting (rather than mere entertainment) of infants who are part of the household and enables nurturing interactions such as feeding, toileting, bathing, playtime, discipline, bedtime rituals and comforting when they awake (Amato & Gilbreth, 1999;Kelly & Lamb, 2000;Smyth, 2004).…”
Section: Family Court Judges' Decisions Regarding Post-separation Carmentioning
confidence: 89%
“…Pruett, Ebling, and Insabella (2004) studied 161 families and found that preschoolers responded to post-divorce parenting plans very individually. Girls with overnight visits and more caregivers showed fewer adjustment problems; boys showed no such benefits.…”
Section: Implications For Young Children Of Divorcementioning
confidence: 98%